FIND THE ANSWERS

Solve (x+y)^3-2(x+y)-(x^3-2x)?

Answer this question

Do you know the correct answer? Make money answering questions! Join now.
  • Solve (x+y)^3-2(x+y)-(x^3-2x)?


Answers

Find right answers right now! Solve (x+y)^3-2(x+y)-(x^3-2x)? More questions about Science & Mathematics
Read more
Positive: 40 %
Solve the two equations simultaneously. y=2x^2 ... 3) x=(-5/2+1)/3=-1/2," "x=(5+1)/3=2 Therefore the solutions are x=-1/2," " y=-5/2 ... Socratic start? ...
Read more
Positive: 37 %

More resources

Unformatted text preview: x- 1 / 2 x- 3 / 2 y = Z 9 2 x- 1 / 2 dx x- 3 / 2 y = 9 x 1 / 2 + c ; y = 9 x 2 + cx 3 / 2 dsolve({2x*(diff(y(x), x))-3*y(x) = 9x ...
Read more
Positive: 40 %
Solve for x in terms of y . x 2 = y- 2 x = p y- 2 x can be solved if and only if y 2 . 6 Example ... Solve for x in terms of y . x 2 = y- 2 x = p y- 2 x ...
Read more
Positive: 35 %
Find right answers right now! Solve (x+y)^3-2(x+y)-(x^3-2x)? More questions about Science & Mathematics
Read more
Positive: 21 %
... ,\\ y_2 & = 2^{111x_2},\\ y_3 & = 2^{111x_3}.\\ \end{align} Therefore $$ y_1 y_2 y_3 = 2^{111x_1} 2^{111x_2} 2^{111x_3} ... how to solve $x^2 = 3x + 4$ 0.
Read more
Positive: 10 %

Show more results